Gut Metabolite Urolithin A Inhibits Osteoclastogenesis and Senile Osteoporosis by Enhancing the Autophagy Capacity of Bone Marrow Macrophages - Tao, Huaqiang; Tao, Yunxia; Yang, Chen; Li, Wenming; Zhang, Wei; Li, Xueyan; Gu, Ye; Hong, Yujing; Yang, Huilin; Liu, Yu; Yang, Xing; Geng, Dechun (Frontiers in Pharmacology, 2022)
Senile osteoporosis (SOP) is a systemic bone disease that is significantly associated with age and eventually leads to deteriorated bone strength and increased fracture risk. Urolithin A (Uro-A) is a gut microbiome-derived compound that is mainly produced from pomegranates and some nuts. Uro-A has attracted great attention in recent years in view of its protective effects on aging-related diseases, including muscle dysfunction, kidney disease and knee injury. However, its protective influence and possible mechanisms in senile osteoporosis remain unclear. Our study describes the beneficial effect of Uro-A on bone marrow macrophages (BMMs). The in vitro results demonstrated that Uro-A inhibited receptor activator for nuclear factor-κB ligand (RANKL)-induced osteoclastogenesis in BMMs in a concentration-dependent manner. Uro-A significantly reduced the expression of osteoclast-related genes and bone resorption. Mechanistically, we found that the autophagy ability of BMMs was significantly enhanced in the early stage of Uro-A treatment, accompanied by the activation of LC3 and Beclin 1. At the same time, this enhanced autophagy activity was maintained until the later stage after stimulation with RANKL. Furthermore, we found that the MARK signaling pathway was blocked by Uro-A treatment. In a mouse model of aging, Uro-A effectively inhibited bone loss in the proximal femur, spine and tibia of aging mice. These results indicated that Uro-A is a robust and effective treatment for preventing senile osteoporosis bone loss.